2014
DOI: 10.19030/jabr.v30i3.8559
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare RFID In Germany: An Integrated Pharmaceutical Supply Chain Perspective

Abstract: Todays healthcare environments are characterized by a variety of products, services, and associated data and information that are transferred across many healthcare sector participants. Pharmaceutical supply chains in particular are one example of fragmented information flows among supply chain participants. Pharmaceutical supply chain processes have a crucial influence on medication quality and ultimate patient outcomes. When manufacturing problems arise, temperature control cannot be maintained throughout th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“… 27 A cross-country RFID-tag study was conducted in Germany, allowing all supply chain actors to communicate with a central database. 30 In Hong Kong, case studies showed promising results for the use of RFID tags and a global sharing mechanism, including an alert in the event of unsuccessfully matched information. 31 India implemented barcoding on drugs for export only, using codes on all packaging levels, but without a database.…”
Section: Resultsmentioning
confidence: 99%
“… 27 A cross-country RFID-tag study was conducted in Germany, allowing all supply chain actors to communicate with a central database. 30 In Hong Kong, case studies showed promising results for the use of RFID tags and a global sharing mechanism, including an alert in the event of unsuccessfully matched information. 31 India implemented barcoding on drugs for export only, using codes on all packaging levels, but without a database.…”
Section: Resultsmentioning
confidence: 99%
“…These factors will help change the PSC design for greater efficiency, safety, and quality [20]. PSC processes have an important influence on the quality of drugs and patients' end-result [24].…”
Section: Implications and Discussionmentioning
confidence: 99%
“…Road / Pallets ( Kheir, 2011;Sharif et al, 2010)/ (Bauer, 2016) Cabinets (Wandalkar et al, 2013) (Chavan et al, 2014;Nelson et al, 2011;Vancea and Viman 2011;Bijwaard et al, 2011;Li and Achen, 2011) Electronic Monitors (Çakici et al, 2011;Chircu et al, 2014;Metzner et al, 2014, Aung et al, 2011Hendrik Haan et al, 2013 ;MingheU et al, 2014;Ruiz-Garcia and Lunadei, 2010;Li et al, 2013, ) Although the analysis of the sub-issues is beyond the scope of this review, some exciting insights into the main logistic issues of the PCC can be obtained from Figure 2. A great deal of academic work involves understanding and suggesting solutions to issue of the PCC (Table 2), classi ied into 7 categories (Technological resources and PCC concepts), represented by different colors, which are: data analyses, cold chain models (with temperature), quality of novel technologies, integration of informatics systems, traceability technologies, supply chain models (without temperature) and analytical technologic process.…”
Section: Service (Lo-s)mentioning
confidence: 99%